Climate change awareness and solar energy adoption of household - Zainudin, Norzalina; Md Jusoh, Zuroni; Zainalaludin, Zumilah; Osman, Syuhaily; Nordin, Nurnaddia; Paim, Laily; Ramasamya, Abinasan (NADIA, 2019)
As climate change issues continue to gain prevalence, consumers are exposed daily to messages encouraging themto green their behaviours, whether through making home improvements, driving less, or purchasing environmentally friendly products. In spite of this encouragement and an awareness of climate change and other environmental issues, many consumers still do not adopt environmentally friendly behaviours. Specifically in terms of green energy adoption, while consumers might acknowledge of climate change issues, many do not take the steps to adopt energy from renewable source such solar photovoltaic. Finding waysto bridge the gap between environmental awareness and behaviour change is critical in increasing the adoption of environmentally sustainable behaviours, including purchases of solar PV products. A total of 153 face to face interviewed questionnaires were distributed to urban Malaysian household in Selangor, Malaysia. Through survey experiment, this capstone explored consumers’ evaluations of solar energy photovoltaic through net energy metering program, text indicating that the product was environmentally friendly and effective. The findings of this research indicate that consumers more positively evaluate solar energy over non-renewable energy sources. This understanding of the connections between environmental consciousness and green purchasing provides insight for bridging the gap between environmental awareness and behaviour change of household.